Foto con signora. Omaggio a 'L’amore fugge' di François Truffaut (Materiali di Estetica. Terza serie, 2014)
Love on the Run (L'amour en fuite, France, 1979) is François Truffaut’s latest film featuring the fictional character of Antoine Doinel. By means of flashbacks from other films of the «Doinel series»,  the film goes over the protagonist’s love mishaps. Picture with a Lady is a drama experiment applied to movie making, a fictional creation that makes its way through what was unrevealed in Love on the Run, and tells, in the folds of the unsaid, a love story imagined but already implied in the film. A love story both inevitable and impossible. KEYWORDS: Truffaut; Doinel; Amore; Montaggio;